Mr Majeika And the lost spell book - Carenter, Humphrey; Rodgers, Frank (london Puffin books ltd, 2010)
Fun and magic combine as usual in this new Mr Majeika story. The pupils in Class 3 at St Barty's School are not impressed when their headteacher imposes strict rules of behaviour for Halloween. Mr Majeika uses a little magic to make the evening memorable but nasty Hamish Bigmore tells the local press and gets the wizard-teacher the sack. School without magic seems rather boring and Mr Majeika doesn't last long in the other jobs he tries. His long-time enemy, Wilhelmina Warlock is clearly behindall the trouble; she and the dreaded Hamish must be defeated before life can return to normal.